Modified Zebra Optimization Algorithm via Design Operators for Modern Power System Planning Problem Solution - Yunus Balci; Serhat Duman (IEEE Access, 2025)
Transmission Expansion Planning (TEP) is a key aspect in securing the reliability and efficiency of current-day power systems when dealing with the growing energy needs and energy security. This work presents an advanced optimization framework, which incorporates the Zebra Optimization Algorithm (ZOA) with two new improvement strategies: the FFDB method and OBL strategies. The FFDB mechanism improves it to balance exploitation and exploration by fine-tuning the contribution of the fitness and distance metrics using the fuzzy logic technique. At the same time, OBL increases population diversity and accelerates convergence by strategically distributing across the solution space. The combination of these elements is the FFDBZOA-OBL algorithm. The proposed algorithm was thoroughly validated in two experiment setups. First, its optimization performance was evaluated on the CEC2020 and CEC2022 benchmarks, showing a better performance than existing methods. Second, the FFDBZOA-OBL was applied to the real-world TEP problem, demonstrating the ability to minimize the costs of investment mechanisms while adjusting to the changing state of affairs in the market and supporting the resilience of local energy supply. Additionally, the robustness and significance of the proposed method are also supported by statistical analysis in the form of Wilcoxon and Friedman tests. Based on the results of the FFDBZOA-OBL approach, the obtained solution is a very competitive and adaptive one in terms of benchmark and practical power system optimization problems.